Искусственный эквивалент кожи на основе акриловых гидрогелей с иммобилизованными наночастицами серебра и клетками человека - Папуга, А.Е.; Самченко, Ю.М.; Ульберг, З.Р.; Рубан, Т.А.; Козинец, Г.П.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2014)
Aims. The purpose of this work was to create new and improved dermal equivalents which could be used for therapy of massive burns. Methods. As the scaffolds we used polyacrylamide hydrogels. Additional components (nanoparticles or metal ions) were added into the hydrogels. Biocompatibility of obtained specimens and their influence on cell survival was investigated by using microscopic examinations and cytochemical staining. As a cell component of the dermal equivalents we used: 1) original cell line 4BL; 2) primary human skin fibroblasts. Results. I was obtained maximum stimulation of cell proliferation at the presence in scaffold of colloid silver at the concentration of 25 ug/g dry weight. Conclusions. A positive effect of silver nanoparticles in the composition of hydrogels on cell survival and proliferation was demonstrated.

Key words: scaffold, dermal equivalents, human cells, hydrogel, burn.